Smart antennas with MATLAB?, Second Edition - Gross, Frank B. (McGraw-Hill Education LLC., 2015)
Fully revised for the latest advances in the field, this comprehensive professional reference offers a complete overview of the principles behind smart antenna design and operation and is the only book to addresses reconfigurable antennas and vector antennas.